1979
DOI: 10.1152/ajpendo.1979.237.3.e273
|View full text |Cite
|
Sign up to set email alerts
|

Maternal starvation and progesterone secretion, litter size, and growth in the pig.

Abstract: The relationships of maternal nutrition and progesterone secretion to prenatal fetal loss and neonatal survival and growth were investigated in domesticated pigs that normally experience 40% fetal loss. Yorkshire pigs were subjected to prolonged starvation (40 days; 0 kcal/day; water only) in either the middle third or last third of pregnancy and then gradually realimented to a full diet and allowed to advance to parturition; controls received a full diet (7,028 kcal/day) throughout gestation. Pregnancies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…Structural and functional properties of ovine corpora lutea of pregnancy were not altered by plane of nutrition. Moreover, maternal nutrient restriction during the middle third of gestation in pigs had no effect on ovarian progesterone production or fetal survival [46]. Morphometric data for sheep corpora lutea are consistent with previous reports summarized by Sawyer [23].…”
Section: Discussionsupporting
confidence: 85%
“…Structural and functional properties of ovine corpora lutea of pregnancy were not altered by plane of nutrition. Moreover, maternal nutrient restriction during the middle third of gestation in pigs had no effect on ovarian progesterone production or fetal survival [46]. Morphometric data for sheep corpora lutea are consistent with previous reports summarized by Sawyer [23].…”
Section: Discussionsupporting
confidence: 85%
“…Reduced neonatal survivability, growth and development associated with low birth weights have led to considerable interest in factors affecting fetal growth. Some factors shown in previous investigations to affect fetal growth are uterine space (Perry and Rowell, 1969), uterine environment (Walton and Hammond, 1938;GregOry et al, 1978)) genetic potential (Walton and Hammond, 1938), nutrition (Wallace, 1948;Prior and Christenson, 1976;Hard and AnderSon, 1979;Korimlk et al, 1981) and blood flow to the fetus (Wigglesworth, 1964;Wootton et al,, 1977).…”
mentioning
confidence: 98%
“…Without the fasted control group, the effects of maternal diabetes would be confounded due to elevated levels of both glucose and free fatty acids. Other studies have shown that 40 d fasting during a period of rapid fetal growth in the pig had no affect on total litter weight at birth (Hard and Anderson, 1979). In the present study, sows were fasted for 20 d during a period of slower fetal growth.…”
Section: Introductionmentioning
confidence: 46%